2014
DOI: 10.4319/lo.2014.59.4.1434
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of larval transport into a rip‐channeled surf zone

Abstract: Competent larvae of intertidal invertebrates have to migrate toward shore for settlement; however, their migration through the surf zone is not understood. We investigated larval transport mechanisms at a ripchanneled beach. Because tracking larvae in the surf zone is infeasible, we used a three-dimensional biophysical model to simulate the processes. The coupled model consists of a physical module for currents and waves, and a biological module for adding larval traits and behaviors as well as Stokes drift to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 32 publications
(42 reference statements)
6
66
0
Order By: Relevance
“…We hypothesize that the very high concentrations of Pseudonitzschia in the rip current samples is due to the interaction of the rip current flow system with floating cells caught by bubbles. Results from a bio-physical model of this surf zone are consistent with this hypothesis (Fujimura et al, 2014).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…We hypothesize that the very high concentrations of Pseudonitzschia in the rip current samples is due to the interaction of the rip current flow system with floating cells caught by bubbles. Results from a bio-physical model of this surf zone are consistent with this hypothesis (Fujimura et al, 2014).…”
Section: Discussionsupporting
confidence: 75%
“…The physical oceanographic results and models have been described in several previous papers (Fujimura et al, 2013(Fujimura et al, , 2014MacMahan et al, 2009;Reniers et al, 2009Reniers et al, , 2010Shanks et al, 2015). Here we compare Pseudo-nitzschia spp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although numerical simulations were based on light winds, our companion study demonstrated that simulated larvae also enter surf zones during windy conditions [34]. Simulated larvae near the surface were transported towards the surf zone by surface flow generated by wind stress and wave transport (Stokes drift).…”
Section: Discussionmentioning
confidence: 99%